Mantodea of Egypt - Mohammad, Salwa Kamal; Alla, Sohair Mohammad Gad; El-Hamouly, Hayam; Ehrmann, Reinhard; Nasser, Mohamed Gemal El-Den (Zootaxa, 2011)
The Mantodea of Egypt were studied by examining and identifying specimens from four main Egyptian collections and some of those preserved in international museums, collecting specimens from various parts of the country between July 2007 and April 2010, and previous Egyptian records. We found 60 species belonging to 21 genera and 4 families. Eremiaphilidae included 31 species in 2 genera with one new record from Egypt, Eremiaphila gigas; Empusidae, 7 species in 4 genera; Mantidae, 18 species in 13 genera with one new species, Elaea solimani; and Tarachodidae, 3 species in 2 genera. We provide identification keys for Egyptian taxa, data on the material examined, the world distribution, synonyms and a description of the new species.